ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIK SISWA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Ramadhan, Akmal; Anwar, Saepul; Falak, Agam Fajrul (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this study is that researchers want to analyze the ability of students' mathematical problems in solving problems on the SPLDV material. This research is a descriptive study conducted at IKIP Siliwangi, with data analysis used is descriptive qualitative analysis. The subjects of this study were students who took part in mathematics learning in the 2019-2020 academic year. The results of the analysis in this study indicate that each indicator in problem management shows high results. In the first indicator, namely understanding the problem, the average ability is 67%. In the second indicator, planning, the average ability reaches 71%. In the third indicator that makes achievements, students can reach 63%. The last indicator, which is checking again, reaches an average of 70%. When viewed in total, students' mathematical analysis skills can be displayed very high.